2016
DOI: 10.1051/0004-6361/201526326
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging discovery of a second planet candidate around the possibly transiting planet host CVSO 30

Abstract: Context. Direct imaging has developed into a very successful technique for the detection of exoplanets in wide orbits, especially around young stars. Directly imaged planets can be both followed astrometrically on their orbits and observed spectroscopically and thus provide an essential tool for our understanding of the early solar system. Aims. We surveyed the 25 Ori association for direct-imaging companions. This association has an age of only few million years. Among other targets, we observed CVSO 30, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 152 publications
(131 reference statements)
2
27
0
Order By: Relevance
“…As a result, we could confirm the detection of a transit-like signal within the light curve of CVSO 30, which was first found by van Eyken et al (2012). Schmidt et al (2016) discovered an additional wide companion planet candidate via direct imaging. CVSO 30, which is also known as PTFO 8-8695, is a weak-line T Tauri star with spectral type E-mail: richard.bischoff@uni-jena.de M3 (Briceño et al 2005), which showed initially brightness dips of ∼ 35 mmag every ∼ 10.8 h lasting about 100 min.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…As a result, we could confirm the detection of a transit-like signal within the light curve of CVSO 30, which was first found by van Eyken et al (2012). Schmidt et al (2016) discovered an additional wide companion planet candidate via direct imaging. CVSO 30, which is also known as PTFO 8-8695, is a weak-line T Tauri star with spectral type E-mail: richard.bischoff@uni-jena.de M3 (Briceño et al 2005), which showed initially brightness dips of ∼ 35 mmag every ∼ 10.8 h lasting about 100 min.…”
Section: Introductionsupporting
confidence: 68%
“…We used high-resolution direct imaging data with adaptive optics of CVSO 30 from the ESO archive to estimate an upper limit on the possible separation, if CVSO 30 consists of two equally bright stars. The target was observed with NACO at ESO's VLT on December 03 2012 in jitter mode, using a jitter-width of 4 arcsec, and the data were presented first in Schmidt et al (2016). According to the ESO ambient conditions database 4 the average DIMM seeing was 0.67 ± 0.03 arcsec and the average coherence time of the atmospheric fluctuations was 4.5 ± 0.2 ms during the Ks-band observations.…”
Section: Comparison With Cluster Membersmentioning
confidence: 99%
“…The same conclusion as for V830 Tau b (Donati et al 2016) and K2-33 b (Mann et al 2016) implies that the planet formation and orbital evolution would be generally completed within a few Myr. Recently, Schmidt et al (2016) reported on the dete ction of a putative second planet candidate CVSO 30 c (PTFO 8-8695 c) orbiting at 662 au. If their planet candidate and our identification of a transiting planet are both true, PTFO8-8695 is the first system where a close-in planet and a wide separation planet are found to be orbiting the same star.…”
Section: Ptfo 8-8695 Bmentioning
confidence: 99%
“…This point source was claimed to be a potential planetary-mass object(Schmidt et al 2016). Subsequent analysis of its colors showed that it is a background star (Lee & Chiang 2018).…”
mentioning
confidence: 99%